A sequence planning method for five-axis hybrid manufacturing of complex structural parts. (February 2020) - Liu, Changqing; Li, Yingguang; Jiang, Sen; Li, Zhongyu; Xu, Ke
The concept of additive–subtractive hybrid manufacturing provides a new idea for the manufacturing of high-precision complex structural parts. Currently, under the five-axis additive–subtractive hybrid manufacturing mode, existing research work concerned with sequence planning issues have limitations. This article presents a sequence planning method for hybrid manufacturing of complex structural parts with high precision. The initial printing direction of parts was determined based on an iterative search method and the initial hybrid manufacturing sequence was constructed by part volume decomposition, which solved the coupling problem of printing direction decision and machinability calculation. Under the constraint of tool accessibility, the whole planning of the hybrid manufacturing sequence was realized based on greedy algorithm. This method has achieved highly effective planning of the alternative sequence in the process of hybrid manufacturing, thus greatly reduced the number of tool changes required and laid a foundation for the realization of highly efficient hybrid manufacturing.